Prodigiosin: unveiling the crimson wonder – a comprehensive journey from diverse bioactivity to synthesis and yield enhancement - Lu, Yonglin; Liu, Derun; Jiang, Renhui; Li, Ziyun; Gao, Xueyan (Frontiers in Microbiology, 2024)
Prodigiosin (PG) is a red tripyrrole pigment from the prodiginine family that has attracted widespread attention due to its excellent biological activities, including anticancer, antibacterial and antialgal activities. The synthesis and production of PG is of particular significance, as it has the potential to be utilized in a number of applications, including those pertaining to clinical drug development, food safety, and environmental management. This paper provides a systematic review of recent research on PG, covering aspects like chemical structure, bioactivity, biosynthesis, gene composition and regulation, and optimization of production conditions, with a particular focus on the biosynthesis and regulation of PG in Serratia marcescens. This provides a solid theoretical basis for the drug development and production of PG, and is expected to promote the further development of PG in medicine and other applications.